A21 ULCERATIVE COLITIS-ASSOCIATED E. COLI PATHOBIONTS POTENTIATE COLITIS IN SUSCEPTIBEL HOSTS. (4th March 2021) - Yang, H; Mirsepasi-Lauridsen, H; Struve, C; Allaire, J M; Sivignon, A; Vogl, W; Bosman, E S; Ma, C; Fotovati, A; Reid, G; Li, X; Petersen, A M; et al.
Abstract: Background: Ulcerative colitis (UC) is a chronic inflammatory condition linked to intestinal microbial dysbiosis, including the expansion of E. coli strains related to extra-intestinal pathogenic E. coli . These "pathobionts" exhibit pathogenic properties, but their potential to promote UC is unclear due to the lack of relevant animal models. Aims: We explored the potential to establish a mouse model of GI infection by the UC-associated E. coli strain p19A, as well as characterize the pathogenic features of p19A. Methods: We used a representative UC pathobiont strain (p19A), and mice lacking single immunoglobulin and toll-interleukin 1 receptor domain (SIGIRR), a deficiency increasing susceptibility to gut infections. Vancomycin-pretreated Sigirr -/ - mice were subsequently gavaged with the control E. coli DH10B (a derivative of commensal strain K-12) or p19A. One day after infection, mice were exposed to 2.5% dextran sodium sulfate (DSS) in their drinking water for another 4 days. Results: Strain p19A was found to adhere to the cecal mucosa of Sigirr - / - mice, causing modest inflammation. Moreover, it dramatically worsened DSS-induced colitis. This potentiation was attenuated using a p19A strain lacking α-hemolysin genes, or when we targeted pathobiont adherence using a p19A strain lacking the adhesin FimH, or following treatment with FimH antagonists. Conclusions: Thus, UC pathobionts adhere to the intestinal mucosa, and worsen the course of colitis in susceptible hosts in a manner dependent on specific virulence factors, including α-hemolysin and FimH. Funding Agencies: CCC, CIHR